Uterine time and subjectivities: an ethnographic account of the uterus in online body-talk and other articulations of reproductive justice in South African feminist publics - De Ruiters, Elthéa (Social Anthropology, 2023)
The uterus is a largely underrepresented and underknown entity in everyday discourses of bodyhood and is usually only spoken of in specialised and/or intimate contexts. This is, however, changing in contemporary popular feminist culture and spaces, especially across networked publics and social media. In South African public life, there is an emerging intimate public where feminists convene and engage in discussion around various issues of concern, in and across various media spaces, in particular social media platforms like Twitter. In the context of increased public focus on sexual and reproductive health and rights (SRHR) in public health and social justice conversations, this research asks how young people's personal experiences and feelings about the uterus are affected by and mediated through public discourses about reproductive health and justice, intergenerational cultural expectations of the uterine body, and vernacular expressions of body-talk that are amplified and circulated in intimate publics like South African Feminist Twitter. Drawing on a multimodal ‘patchwork' ethnographic enquiry (Gökçe and Watanabe, 2022) that aimed to trace the uterus as an entity that comes to matter in various different, but underrecognized ways, research was conducted between December 2019 and January 2021, during covid-related lockdowns. Methods included virtual ethnography on/via Twitter, an online qualitative survey that was disseminated across my broader Twitter network, an arts-informed feminist workshop engaging with depictions of the uterus in society and popular culture and discussions of personal narratives. The feminist vernaculars and body-talk that circulate and are amplified online emphasise negative affects and the “ugly feelings” that people in this public associate with the uterus. Menarche, the first menstrual period, stood out in personal narratives as the beginning of ‘uterine time', that is, the beginning of one's subjective awareness of and interaction with the societal expectations attached to the uterus. The messaging that young menstruators received from elders about their bodies predominantly positioned the physiological change as triggering a social change in which one's personhood is imbricated with risk and danger. What people say about the uterus, both publicly online and privately, suggests the emergence and propagation of a generational feminist vernacular of body-talk that takes on a ‘radical' character through descriptions of organs exerting violence and affective injury. In this generational vernacular, feminist youth describe the organ mainly as a conduit of cisheteropatriarchal violence and as an embodiment of what Gqola (2021) terms the Female Fear Factory, and purposefully emphasise antagonistic relations of the uterus. I show how common vernacular expressions and epithets contribute to the production of collective orientations to the uterus through affective contagion. For many young people with uteruses, the organ is experienced as invoking a sense of personal responsibility for a (gestational) reproductive future which may or may not materialise but is nevertheless inscribed with a host of intergenerational sociocultural expectations. The thesis examines the key themes of expectation, speculation and anticipation that emerged in the research as as dominant modes of feeling that characterise uterine subjectivities, or what it means to have a uterus. Together these modes form a particular subset of affective-temporal orientations to the future (as opposed to hope, destiny and potentiality). I argue that this is an indicator of the marked sense of anxiety that accompanies contemporary life and, for many feminists on Twitter, seems to be embodied in their subjective experiences of the uterus.